Innovation of Nature-Based Civic Education Learning Model at Al-Kautsar IT High School, Ranggo Village, Pajo District, Dompu Regency - Fitriani (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2023)
The study aims to find out the extent of the application of natural-based civic education learning at Al-Kautsar Ranggo IT High School. This type of research is a research and development experimental approach. This is based on the fact that the experimental method is an appropriate and accurate method to fulfill the function of science, namely explaining, predicting, and controlling. The experimental method has the most strict and transparent structure. The results of the study obtained that the nature of each learning process, the child is allowed to creatively develop the talents and abilities that each student has, because in the learning process the teacher does not ask the student to be something, but gives the student freedom to become something, the teacher only supervises And teaches students to develop the talents they need